The spatial dimension of maritime connectivity: The case of Northern Europe and the Mediterranean - Dial, Rania; de Oliveira, Gabriel; Schaffar, Alexandra (Canadian Journal of Regional Science / Revue canadienne des sciences régionales)

(untitled) (Canadian Regional Science Association / Association canadienne des sciences régionales, 2021)
The aim of this study is to understand how spatial effects influence maritime connectivity. We use a spatial econometric model on panel data for a sample of 114 countries over the period 2004-2017. The results show that there are positive interaction effects that describe a center-periphery relation. We focus specifically on two regions: Northern Europe and the Mediterranean. The results for these two regions indicate substantial differences. In Northern Europe, there is a significant positive spatial dependence with positive spillover effects. Conversely, the Mediterranean region is characterized by a negative spatial dependence, leading to strong competition between countries.